2009
DOI: 10.1128/jcm.00887-09
|View full text |Cite
|
Sign up to set email alerts
|

Role of Deletion Located between the Intermediate and Middle Regions of the Helicobacter pylori vacA Gene in Cases of Gastroduodenal Diseases

Abstract: Gastric cancer arises through steps related to the presence of a chronic Helicobacter pylori infection, which leads to the precursor lesion, atrophic gastritis. The progression of gastric mucosal atrophy varies within and between different populations; and the differences relate to differences in H. pylori virulence, host genetic factors, and/or environmental factors. The important H. pylori virulence factors and host genetic factors are related to an increased inflammatory response and include the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
94
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(105 citation statements)
references
References 29 publications
10
94
0
1
Order By: Relevance
“…Strains with the particular vacA genotypes have been found to be good markers for gastroduodenal disease (Atherton et al, 1995). Ogiwara et al (2009) showed that the vacAd1 allele could be considered a more sensitive independent biomarker in the development of gastroduodenal disease, and LatifiNavid et al (2013) have also recently reported that the vacA d1/-i1 alleles from strains with European ancestry could be considered good markers for gastric cancer in Ardabil and Mazanderan (high incidence areas of GC in Iran) (Ogiwara et al, 2009;Latifi-Navid et al, 2013). In the present study, the genotype of the vacA d region was evaluated in H pylori isolated from patients with gastric adenocarcinoma, PUD and gastritis (control group) in East Azerbaijan in the Northwest of Iran.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Strains with the particular vacA genotypes have been found to be good markers for gastroduodenal disease (Atherton et al, 1995). Ogiwara et al (2009) showed that the vacAd1 allele could be considered a more sensitive independent biomarker in the development of gastroduodenal disease, and LatifiNavid et al (2013) have also recently reported that the vacA d1/-i1 alleles from strains with European ancestry could be considered good markers for gastric cancer in Ardabil and Mazanderan (high incidence areas of GC in Iran) (Ogiwara et al, 2009;Latifi-Navid et al, 2013). In the present study, the genotype of the vacA d region was evaluated in H pylori isolated from patients with gastric adenocarcinoma, PUD and gastritis (control group) in East Azerbaijan in the Northwest of Iran.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the genotype of the vacA d region was evaluated in H pylori isolated from patients with gastric adenocarcinoma, PUD and gastritis (control group) in East Azerbaijan in the Northwest of Iran. First, the frequency of vacA d1 was determined and compared with that reported in two previous studies (Ogiwara et al, 2009;Latifi-Navid et al, 2013). In this study, the frequencies for the vacA d1 and d2 alleles were 43.37% and 56/63% respectively in patients with gastric adenocarcinoma, peptic ulcer and gastritis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The d region is divided into d1 and d2 with d1 identified a risk factor for GC and PUD in Western strains. Nearly all H pylori isolates from East Asia have been found to have a genotype of vacA d1 (Ogiwara et al, 2009). Our results showed that the overall prevalence of vacA d1 genotype is lower than that found in Iran this could contribute to the differences in gastric cancer rates seen between these communities.…”
Section: Dear Editormentioning
confidence: 99%